Analisis Naratif Video Animasi â€˜Gunungâ€™ di Saluran Gromore Studio Series: Kajian Futurologi terhadap Media Pembelajaran Menyimak - Rahmawati Mulyaningtyas; Sudtida Tanompol (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
The use of animated videos featuring the legends of â€œmountainsâ€ can serve as a relevant alternative medium for enhancing listening skills while simultaneously instilling local cultural values in students. This study analyzes the narrative structure of mountain legend animations from the Gromore Studio Series YouTube channel, as well as the potential and challenges of using such videos as listening comprehension learning media. A descriptive qualitative approach with narrative analysis was employed. The data sources consisted of three animated videos titled Legenda Gunung Merapi, Legenda Gunung Kelud, and Asal-Usul Gunung Arjuna, produced by Gromore Studio Series on YouTube. The analysis was conducted using Tzvetan Todorov's narrative structure theory and educational futurology to assess the media's relevance in future learning contexts. The data analysis process included (a) data reduction, (b) data presentation, and (c) conclusion drawing/verification. Source triangulation was used to ensure data validity. The findings reveal that all three videos follow a complete narrative structure (equilibrium, disruption, recognition, repair, and new equilibrium). Moreover, the videos have the potential to engage students through contextual visualization of folklore and strengthen listening skills via audio-visual support. They also contribute to character building and local value reinforcement. Challenges include limited technological access in schools, teachers' digital media competency gaps, and alignment with current curriculum especially the learning objectives. Therefore, the use of animated videos as learning media must be supported by policies, training, and comprehensive evaluation to ensure their effectiveness and sustainability in enhancing studentsâ€™ listening literacy.